Biological Study of a Nontoxic, Water-Soluble Immunoadjuvant from Mycobacterial Cell Walls - Chedid, L. (1972)
Whole mycobacterial cells, which are used in Freund's complete adjuvant, besides inducing hypersensitivity to tuberculoprotein, also can elicit hyperreactivity to endotoxins, lymphoid hyperplasia, and allergic polyarthritis in rats. The data reported here demonstrate that a potent water-soluble adjuvant obtained from mycobacterial cell walls is also effective in increasing the immune response to viruses, and that it is free of the toxic effects observed with whole mycobacterial cells.